Barrosasaurus casamiquelai gen. et sp. nov., a new titanosaur (Dinosauria, Sauropoda) from the Anacleto Formation (Late Cretaceous: early Campanian) of Sierra Barrosa (Neuquén, Argentina) - Salgado, Leonardo; Coria, Rodolfo A. (Zootaxa, 2009)
A new Late Cretaceous titanosaurian sauropod from the Sierra Barrosa locality (Anacleto Formation, Late Cretaceous, early Campanian) of Neuquén Province, Argentina, Barrosasaurus casamiquelai gen. et sp. nov., is described. The holotype of this species consists of three large and incomplete, although well-preserved, dorsal vertebrae (one probably the third, the next the seventh or eighth, and the last the ninth or tenth). The arrangement of neural arch laminae in the dorsal vertebrae of this titanosaur differs from that present in other genera in the following ways: the spinoprezygapophyseal laminae are well developed in the third vertebra, and relictual in the seventh or eighth vertebra; two spinodiapophyseal laminae are present in the seventh or eighth and in the ninth or tenth vertebrae, the anterior spinodiapophyseal lamina being more strongly developed than the posterior spinodiapophyseal lamina in the ninth or tenth vertebra. These characters, among others, allow the recognition of this individual as a new species of Titanosauria, which increases knowledge of the diversity of titanosaurs in the Late Cretaceous of Patagonia.